The Effects of the Implementation of the Problem Solving Learning Method in Teaching Natural Sciences - Katarina. B. Putica; Dragica D. Trivić (University of Belgrade, Teacher Education Faculty, 2020)
The aim of this paper was to compare the effectiveness of the problem-based teaching method with traditional receptive teaching in the field of natural sciences. Bearing in mind the most frequent problems pupils are faced with when learning natural sciences, and that these problems are mainly the consequence of traditional receptive teaching, four research hypotheses have been proposed in the paper: compared to the traditional receptive teaching, problem-based teaching method promotes better understanding of the academic content of natural sciences (H1), a more positive attitude of students toward natural sciences (H2), better self-regulation of the learning of natural sciences (H3), and a better academic achievement of students in the field natural sciences (H4). The academic achievement of students in the field of natural sciences was considered solely as a quantitative aspect of students' performance, which is why understanding, as one of the levels of qualitative aspect of students' performance, was considered in a separate hypothesis. In order to verify these hypotheses, meta-analysis was conducted. For the purpose of conducting this meta-analysis, the results obtained from 23 scientific papers were used to calculate corresponding mean values of ES for each of the hypotheses. On the basis of the calculated mean values of ES, all four hypotheses, as well as the great potential of the problem-based method to improve the quality of teaching in the field of natural sciences, have been verified.